Knowledge Sharing Between Universiti Kebangsaan Malaysia And Universitas Syiah Kuala: Universitys Role In Creating Future Entrepreneur - Nizam, Ahmad; Farid, Farid; Harmen, Hamdi; Aprilia, Cut; Suryani, Ade Irma; Rakhmawati, Lenny; Jannah, Rauzatul; Rizqi, Muhammad Fauzil; Nabilah, Nabilah; Adnan, Muhd; Yaacob, Salmy Edawati; Ismail, Adawiyah (Jurnal Pengabdian Bakti Akademisi, 2024)
Knowledge sharing session between Universiti Kebangsaan Malaysia and Universitas Syiah Kuala was aimed to exchange knowledge about creating future entrepreneur. The event was held on 21-22 November 2022 at Universiti Kebangsaan Malaysia with 30 people in attendance. It used the public lecture method where both universities share their ideas about the issues and the students also share their involvement in universities entrepreneurship program. The following recommendations were made in response to the issues raised by this activity: student activity units on entrepreneurship should not only teach students about business but also help them develop their entrepreneurial personalities, enhance instructional strategies that inspire students to think creatively, and design events that connect them with students from different universities.